Penegakan Hukum Terhadap Kejahatan Perampokan Dengan Modus Kencan Sesama Jenis Di Kota Palembang - Yulianti, Marini; Zahri, Saipuddin; Hasan, KN Sofyan (Lex Librum : Jurnal Ilmu Hukum, 2023)
This robbery belongs to the category of acts involving the use of violence, which is now becoming increasingly common. The same-sex date robbery, a prison sentence has been imposed on the perpetrator, with a one-year to six-month sentence reduced during full detention. In addition, the accused is asked to remain in custody in accordance with the applicable material criminal provisions and qualify for conviction according to evidence and inspection. Law enforcement against the crime of homophobia is faced with constraints due to its own legal factors, namely the absence of regulations so necessary to enforce the law, and enforcing factors, such as lack of means and facilities, the number of cases, and incomplete files. A situation where public awareness of the law is low and public participation in law enforcement is increasing.